History of trauma is a critical treatment target for individuals at clinical high-risk for psychosis - Zarubin, Vanessa C.; Gupta, Tina; Mittal, Vijay A. (Frontiers in Psychiatry, 2023)
People meeting criteria for a clinical high-risk (CHR) for psychosis syndrome frequently represent a heterogeneous, help-seeking, and dynamic population. Among the numerous symptoms and risk factors for psychosis, exposure to trauma stands out as both highly prevalent and poorly understood. Indeed, while up to 80% of individuals meeting criteria for a CHR syndrome report trauma histories, there is currently limited research dedicated to this specific area. This is particularly problematic as trauma is tied to risk for conversion, leads to a range of clinical issues, and contributes to disability and poor quality of life. Fortunately, recent research in the general population has led to a significant evolution in the way trauma is assessed and understood, and further, some studies have indicated that targeted trauma interventions in formal psychotic disorders are highly effective. However, direct adoption is challenging as the CHR syndrome holds a number of unique concerns (e.g., clinical heterogeneity, developmental trauma), and characteristically, involves a developing pediatric or young adult population that also comes with specific considerations (e.g., living with caregivers, transitionary period in roles). In this “perspective” we frame the issues around understanding trauma in CHR individuals, discuss viable treatments and unique considerations, and provide suggestions for future steps in developing and incorporating trauma-focused interventions in this population.